Pengaruh Green Marketing dan Green Product terhadap Keputusan Pembelian dengan Brand Equity Sebagai Variabel Intervening pada Brand Sejauh Mata Memandang dalam Menghadapi Tren Fast Fashion (Studi Pada Generasi Z) - Billa, Syakila Salsa; Nining Purwaningsih (BUDGETING : Journal of Business, Management and Accounting, 2025)
This research explores consumer views regarding the slow fashion business which is starting to aggressively fight the fast fashion trend. This research examines whether green marketing and green product Sejauh Mata Memandang can be an effective strategy based on the purchasing decisions that consumers will make, and how brand equity Sejauh Mata Memandang if it participates in mediating these two variables. This research is quantitative research with a descriptive approach. The research data was collected from a sample of Generation Z consumers of Sejauh Mata Memandang in Tangerang City, totaling 100 respondents using nonprobability sampling technique and analyzed using SmartPLS 4.0 software. The result of the coefficient of determination R-Square of path model 1 (one) has a value of 0.590, which means that the ability of variables X1 and X2 to explain Z is 59% and, R-Square of path model 2 (two) has a value of 0.683, which means that the ability of X1 and X2 through Z to explain Y is 68.3%. . The results showed that green marketing has no significant effect on purchasing decisions, green products have a significant effect on purchasing decisions, green marketing has a significant effect on brand equity, green products have a significant effect on brand equity, brand equity has a significant effect on purchasing decisions, brand equity successfully mediates green marketing on purchasing decisions significantly, brand equity cannot mediate green products on purchasing decisions significantly. This study concludes that green marketing carried out with sincerity and transparency will build brand value in the eyes of consumers, and the integration of innovative products with the concept of slow fashion can make consumer purchasing decisions without thinking back. These findings provide valuable insights for businesses that run the slow fashion concept to be able to see the consumer's vision of the brand.   Keywords: Brand Equity, Green Marketing, Green Product, Keputusan Pembelian.